أثر الملوحة في تركيز السكريات والبرولين لثلاثة أنماط وراثية من القمح الطري (Triticum aestivum L.) في مرحلة النمو الخضري باستخدام الزراعة المائية - ميهوب, حامد; الله, عثمان عبد; قابقلي, ريعان أحمد (Latakia University Journal -Biological Sciences Series, 2013)
أنجزت هذه الدراسة في عامي 2009-2011 في مخابر كلية العلوم بجامعة تشرين، فتمت زراعة بذار ثلاثة أصناف من القمح الطري (شام8، سخا8، AUS 29639) في مزارع مائية Hydroponics بإضافة محلول هوغلاند Hoagland المغذي إلى وسط الزراعة ضمن غرفة نمو مخبرية لمقارنة تأثير ثلاثة تراكيز ملحية (0-100-200 ميلي مول من ملح كلور الصوديوم) في محتوى السكريات والبرولين خلال ثلاث مراحل من النمو 21 ، 28، 35. لوحظ تراكم البرولين والسكريات في الأصناف الثلاثة المدروسة بازدياد الملوحة خلال المراحل العمرية الثلاث. كانت في الصنف Sham8 بمعدلات أدنى من الصنفين سخا8 و AUS 29639. زاد تركيز البرولين في الصنف Sakha8 بازدياد الملوحة حتى وصل إلى 348% في المرحلة العمرية الثالثة وبتركيز 200 ميللي مول. بلغ أعلى تركيز للبرولين في الصنف AUS 29639 بتركيز 200 ميللي مول إذ وصل إلى 524%. أما بالنسبة للسكريات فقد كانت بأعلى معدلاتها عند الصنف Sakhs8 بتركيز 200 ميللي مول في المرحلة العمرية الأولى إذ كانت النسبة % 238.70 مقارنة بالشاهد. وبلغت 204.34% في المرحلة العمرية الثالثة بتركيز 200 ميللي مول مقارنة بالشاهد. تشير نتائج الدراسة إلى تفوق الأصناف سخا8 و AUS 29639 في تحملها الملوحة وذلك من خلال مراكمة معدلات مناسبة من البرولين والسكريات. وكان الصنف AUS 29639 أكثر مقاومة للملوحة من الصنف Sakhs8 كما يمكن استخدام هذه النتائج لدراسات فسيولوجية ووراثية أخرى. This study was carried out in 2009-2011, in the laboratories of science faculty - Tishreen University. The seeds of three genotypes: Sham8, Sakha8,AUS 29639 of bread wheat were planted in hydroponic cultures irrigated with Hoagland liquid in a growth chamber to compare the effect of three salt concentrations (0, 100,200 mm of NaCl) on proline and carbohydrate contents in three growth stages 21, 28, 35 of the experiment. There was an increase of proline and carbohydrate contents in all cultivars with increased salinity during the three growth stages of plants. Proline contents increased in Sham8 with low rates compare with Sakha8, AUS 29639. It increased in Sakha8 with the increase of salinity which reached 348% in the third growth stage in concentration 200 mm NaCl, while Proline concentration reached the highest value in AUS 29639 (524%). The carbohydrate content reached the highest value in Sakha8 in NaCl concentration 200 in the first growth stage (238070%) compared with the control, and (204.34%) in third stage in NaCl concentration 200mM compare with the control. The results of the study indicate the superiority of Sakha8, AUS 29639 in salt tolerance through accumulating suitable rates of proline and carbohydrates. AUS 29639 was more resistant to salt stress than Sakha8. We may use these results later in other physiological and genetical studies.